(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
As ever many modern brain researchers are convinced that neurophyiological processes determine human action, and hence they make efforts to grasp brain processes by using highly developed technical means in order to give a scientific description of these processes. This approach refers to natural laws and misinterprets scientific performance as decipher act of the given world (implying that the given world is governed by laws that are recognisable by the human mind). This traditional understanding of science is not only found in natural science, but also in philosophy; nevertheless this understanding is mistaken. In our paper we give a sketch of an adequate understanding of science formulated in terms of Constructive Realism, a new approach in philosophy of science. In this epistemological approach the understanding of science as a description system is replaced by the view of science as the process of replacing scopes of the given world by constructed microworlds. This view changes the idea of knowledge that is no longer the correspondence between proposition and fact, but the insight into the principles (prerequisites) of data structure. Nach wie vor sind viele moderne Hirnforscher von der neurophysiologischen Determiniertheit menschlichen Handelns überzeugt, weshalb sie es auch mithilfe technisch hochentwickelter Messverfahren in naturwissenschaftlichen Beschreibungssystemen eindeutig zu erfassen versuchen. Wer allerdings auf chemisch-physikalische Naturgesetze rekurriert, der begreift wissenschaftliches Handeln offensichtlich als Enträtselungs- und Entschlüsselungsakt der ontischen Welt vorgefertigter Naturgesetze. Da sich aber diese zweifellos traditionelle Interpretation von Wissenschaft als grobes epistemologisches Missverständnis erweist, wird sie in unserem Beitrag thematisiert, mithilfe der Argumentationsstrategien des „Konstruktiven Realismus“ kritisch diskutiert und durch einen fruchtbareren wissenschaftstheoretischen Neuzugang ersetzt. Seit Benjamin Libet in Experimenten nachweisen konnte, dass jeder bewussten Handlungsentscheidung Hirnaktivitäten vorausgehen, welche die Handlung bereits festgelegt haben, zeichnet sich in der Hirnforschung eine Revolution des Menschenbildes ab. Immer mehr Wissenschaftler postulieren jetzt nämlich heftiger denn je, dass unsere Handlungen keinesfalls „willentlich frei“ sein können, sondern dass sie eindeutig neurophysiologisch determiniert wären.